Performance analysis of solar car considering the environmental impact - Islam, Mahmudul; Fahim, Mohammad Shakhawat Hossain; Tamim, MD Tazzammul Hossain; Sakib, Nazmus (Brac University, 2021)
This thesis is submitted in partial fulfillment of the requirements for the degree of Bachelor of Science in Electrical and Electronic Engineering, 2021.